Changes in alcohol consumption associated with social distancing and self‐isolation policies triggered by COVID‐19 in South Australia: a wastewater analysis study. (1st October 2020) - Bade, Richard; Simpson, Bradley S.; Ghetia, Maulik; Nguyen, Lynn; White, Jason M.; Gerber, Cobus
Abstract: Aim: To assess the effects of social distancing and social isolation policies triggered by COVID‐19 on alcohol consumption using wastewater analysis in Adelaide, South Australia. Design: Longitudinal quantitative analysis of influent wastewater data for alcohol concentration. Setting: Adelaide, South Australia. Participants: Wastewater catchment area representative of 1.1 million inhabitants. Measurements: Twenty‐four hour composite influent wastewater samples were collected from four wastewater treatment plants in Adelaide, South Australia for 7 consecutive days (Wednesday–Tuesday) every 2 months from April 2016–April 2020. The alcohol metabolite ethyl sulfate was measured in samples using chromatography–tandem mass spectrometry. Data were population‐weighted adjusted with consumption expressed as standard drinks/day/1000 people. Weekly consumption and weekend to mid‐week consumption ratios were analysed to identify changes in weekday alcohol use pattern. Findings: Estimated weekend alcohol consumption was significantly lower (698 standard drinks/day/1000 people) after self‐isolation measures were enforced in April 2020 compared with the preceding sampling period in February 2020 (1047 standard drinks/day/1000 people), P < 0.05. Weekend to midweek consumption ratio was 12% lower than the average ratio compared with all previous sampling periods. April 2020 recorded the lowest alcohol consumption relative to April in previous years, dating back to 2016. Conclusions: Wastewater analysis suggests that introduction of social distancing and isolation policies triggered by COVID‐19 in Adelaide, South Australia, was associated with a decrease in population‐level weekend alcohol consumption.